A survey of food bank operations in five Canadian cities - Tarasuk, Valerie (BMC Public Health, 2014)
BACKGROUND: Food banks have emerged in response to growing food insecurity among low-income groups in many affluent nations, but their ability to manage this problem is questionable. In Canada, in the absence of public programs and policy interventions, food banks are the only source of immediate assistance for households struggling to meet food needs, but there are many indications that this response is insufficient. The purpose of this study was to examine the factors that facilitate and limit food bank operations in five Canadian cities and appraise the potential of these initiatives to meet food needs. METHODS: An inventory of charitable food provisioning in Halifax, Quebec City, Toronto, Edmonton, and Victoria, Canada was conducted in 2010. Of the 517 agencies that participated in a telephone survey of their operations, 340 were running grocery programs. Multivariate regression analyses were conducted to determine the association between program characteristics, volume of service, and indicators of strain in food banks’ abilities to consistently achieve the standards of assistance they had established. RESULTS: Extensive, well-established food bank activities were charted in each city, with the numbers of people assisted ranging from 7,111 in Halifax to 90,141 in Toronto per month. Seventy-two percent of agencies indicated that clients needed more food than they provided. The number of people served by any one agency in the course of a month was positively associated with the proportion of food distributed that came from donations (beta 0.0143, SE 0.0024, p 0.0041) and the number of volunteers working in the agency (beta 0.0630, SE 0.0159, p 0.0167). Food banks only achieved equilibrium between supply and demand when they contained demand through restrictions on client access. When access to assistance was less restricted, the odds of food banks running out of food and invoking measures to ration remaining supplies and restrict access rose significantly. CONCLUSIONS: Despite their extensive history, food banks in Canada remain dependent on donations and volunteers, with available resources quickly exhausted in the face of agencies’ efforts to more fully meet clients’ needs. Food banks have limited capacity to respond to the needs of those who seek assistance.